2013
DOI: 10.1093/hmg/ddt008
|View full text |Cite
|
Sign up to set email alerts
|

Altered localization, abnormal modification and loss of function of Sigma receptor-1 in amyotrophic lateral sclerosis

Abstract: Intracellular accumulations of mutant, misfolded proteins are major pathological hallmarks of amyotrophic lateral sclerosis (ALS) and related disorders. Recently, mutations in Sigma receptor 1 (SigR1) have been found to cause a form of ALS and frontotemporal lobar degeneration (FTLD). Our goal was to pinpoint alterations and modifications of SigR1 in ALS and to determine how these changes contribute to the pathogenesis of ALS. In the present study, we found that levels of the SigR1 protein were reduced in lumb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
138
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(153 citation statements)
references
References 82 publications
15
138
0
Order By: Relevance
“…[13][14][15][16]51). Indeed, the key mechanisms linking Sig1Rs to neuronal survival involve their translocation from the MAM to plasma membrane, where they bind and modulate ion channels and receptors (14).…”
Section: Discussionmentioning
confidence: 99%
“…[13][14][15][16]51). Indeed, the key mechanisms linking Sig1Rs to neuronal survival involve their translocation from the MAM to plasma membrane, where they bind and modulate ion channels and receptors (14).…”
Section: Discussionmentioning
confidence: 99%
“…The S1R has been established as a therapeutic target for many neurodegenerative conditions in humans that involve various forms of cellular metabolic stress, including amyotrophic lateral sclerosis (Al-Saif et al, 2011;Mancuso et al, 2012;Mavlyutov et al, 2013Mavlyutov et al, , 2015Prause et al, 2013;Gromek et al, 2014;Fukunaga et al, 2015;Mishra et al, 2015), frontotemporal lobar dementia (Luty et al, 2010), Alzheimer disease (Feher et al, 2012;Yin et al, 2015), Parkinson disease (Mishina et al, 2005;Mori et al, 2012), retinal neurodegeneration (Smith et al, 2008;Mavlyutov et al, 2011;Shimazawa et al, 2015), addiction to drugs of abuse (Navarro et al, 2010;Nguyen et al, 2015), and psychiatric disorders (Tsai et al, 2014) (Fig. 1).…”
Section: Introductionmentioning
confidence: 99%
“…Al-Saif et al reported that overexpression of σ 1 R E102Q in NSC34 cells, a motor neuron-like cell line, enhanced vulnerability to ER stress and reduced cell viability [13]. Prause et al also reported abnormal distribution of endogenous σ 1 R in fibroblasts of ALS8 patients (OMIM #608627) [14]. Although these observations suggest that mutation or mislocalization of σ 1 R functions in ALS and FTLD pathologies, it is not known whether perturbations of σ 1 R protein compromise motor neuron survival, and if so, what the underlying mechanism is.…”
Section: Introductionmentioning
confidence: 99%